A new torquemeter to measure the influence of heat-treatment on torsional resistance of NiTi endodontic instruments. (December 2017) - La Rosa, G.; Lo Savio, F.; Pedullà, E.; Rapisarda, E.
Abstract: NiTi endodontic rotary instruments have increased flexibility and strength compared with stainless steel instruments, but they seem to be vulnerable to fracture in clinical situations. Heat treatment (thermal processing) is one of the most fundamental approaches toward adjusting the transition temperatures of NiTi alloys and affecting the fatigue and torsional resistance of NiTi endodontic files. In recent years, novel thermo-mechanical processing and manufacturing technologies such as controlled memory wire (CM-wire), M-Wire and electrical discharge machining (EDM) have been developed to optimize the microstructure of NiTi alloys and their mechanical properties. Aim of this work was to investigate the torsional resistance (maximum torque load, and angular rotation) of NiTi instruments made by different thermo-mechanical and manufacturing processes. For this purpose, a torque device able to perform static and dynamic tests of Ni-Ti instruments for root canal treatment was designed and realized, by performing this device through the design and optimization of the single components and on the system globally. Highlights: A new device (torquemeter) for root canal endodontic instruments was designed and realized. A testing campaign was conducted on NiTi heat-treated instruments. The fractures were analyzed by SEM fractography.